Breastfeeding and maternal health outcomes: a systematic review and meta‐analysis. (December 2015) - Chowdhury, Ranadip; Sinha, Bireshwar; Sankar, Mari Jeeva; Taneja, Sunita; Bhandari, Nita; Rollins, Nigel; Bahl, Rajiv; Martines, Jose
Abstract: Aim: To evaluate the effect of breastfeeding on long‐term (breast carcinoma, ovarian carcinoma, osteoporosis and type 2 diabetes mellitus) and short‐term (lactational amenorrhoea, postpartum depression, postpartum weight change) maternal health outcomes. Methods: A systematic literature search was conducted in PubMed, Cochrane Library and CABI databases. Outcome estimates of odds ratios or relative risks or standardised mean differences were pooled. In cases of heterogeneity, subgroup analysis and meta‐regression were explored. Results: Breastfeeding >12 months was associated with reduced risk of breast and ovarian carcinoma by 26% and 37%, respectively. No conclusive evidence of an association between breastfeeding and bone mineral density was found. Breastfeeding was associated with 32% lower risk of type 2 diabetes. Exclusive breastfeeding and predominant breastfeeding were associated with longer duration of amenorrhoea. Shorter duration of breastfeeding was associated with higher risk of postpartum depression. Evidence suggesting an association of breastfeeding with postpartum weight change was lacking. Conclusion: This review supports the hypothesis that breastfeeding is protective against breast and ovarian carcinoma, and exclusive breastfeeding and predominant breastfeeding increase the duration of lactational amenorrhoea. There is evidence that breastfeeding reduces the risk of type 2 diabetes. However, an association between breastfeeding and bone mineral density or maternal depression or postpartum weight change was not evident.